IMPLEMENTASI EVALUASI DIRI SEKOLAH - Poppy Putri Kusumaning Ayu; Akhmad Mu’adin (STAI Sangatta Kutai Timur, 2022)
In the management of educational institutions, of course, the quality of educational institutions that meet the standards that have been set is needed. Measuring the quality of the course required evaluation. School self-evaluation is one of the evaluations that can be done independently by educational institutions. Based on this, the purpose of writing this article is to determine the implementation of school self-evaluation. The writing in this article uses a qualitative approach with the type of library research. Based on the results of the analysis, it was concluded that school self-evaluation is a process of implementing a self-assessment of educational institutions in order to see the strengths and weaknesses of the institution so that it can improve or improve quality. In essence, school self-evaluation is used to identify school achievements, find priority needs and improvements, as data for decision making, and improve the quality of education. Based on the results of the implementation of the School Self Evaluation, schools are able to produce complete and accurate data and evidence to make school work plans that are better, more competitive, and more progressive. After schools are able to formulate programs from their best work plans, they are implemented as much as possible so that the quality of education can be achieved in accordance with the eight national education standards, namely content standards, process standards, educators, and education personnel standards, financing standards, facilities and infrastructure standards, graduate competency standards, management standards, and assessment standards.